Aegilops sharonensis HMW‐GSs with unusually large molecular weight improves bread‐making quality in wheat‐Ae. sharonensis introgression lines. (2nd January 2023) - Li, Yu; Li, Qing; Hu, Qian; Guzman, Carlos; Lin, Na; Xu, Qiang; Zhang, Yazhou; Lan, Jingyu; Tang, Huaping; Qi, Pengfei; Deng, Mei; Ma, Jian; et al.
Abstract: Background: Eighteen wheat ( Triticum aestivum‐Aegilops sharonensis ) introgression lines were generated in the previous study. These lines possessed four types of high molecular weight glutenin subunit (HMW‐GS) combinations consisting of one glutenin from Ae. sharonensis ( Glu‐1S sh ) plus one or more HMW‐GSs from common wheat ( Glu‐A1, Glu‐B1, or Glu‐D1 ). Results: In this study, we conducted quality tests to explore the effects of 1S sh x2.3 and 1S sh y2.9 on the processing quality of 18 wheat‐ Aegilops sharonensis introgression lines. Our data showed that the 1S sh x2.3 and 1S sh y2.9 subunits had a positive effect on gluten and baking quality. The bread volume of all these lines was higher than that of the parental wheat line LM3. In these lines, the HMW‐GS content and the HMW/LMW ratio of 66‐36‐11 were higher than those of LM3, and the 66‐36‐11 line exhibited greatly improved quality parameters in comparison with the parent LM3. Conclusion: These results demonstrated that the 1S sh x2.3 and 1S sh y2.9 subunits from Ae. sharonensis contributed immensely to gluten strength and bread‐baking quality, and proved a positive relationship between the HMW‐GS sizes and their effects on dough strength in vivo . The materials developed could be used by breeding programs aiming to increase bread‐making quality. © 2022 Society of Chemical Industry.